Genitourinary Prosthetic Use among Prostate Cancer Survivors Treated with Radical Prostatectomy. Issue 2 (March 2019) - Aliperti, Louis A.; Patil, Dattatraya; Filson, Christopher P.; Hartsell, Lindsey M.; Carney, Kenneth J.; Sanda, Martin G.; Mehta, Akanksha
Abstract: Introduction: Erectile dysfunction and urinary incontinence are well-known side effects of radical prostatectomy that, when refractory to medical therapy, can be addressed by major genitourinary prosthetic surgery (urethral slings, artificial urinary sphincters, penile prostheses). Although these procedures have been evaluated in single institution studies, population based analyses regarding their use have been sporadic. Thus, we characterized post-prostatectomy genitourinary prosthetic surgery in a contemporary, population based cohort of men with private insurance. Methods: Using MarketScan® Commercial Claims data we identified men who underwent radical prostatectomy between 2009 and 2010 based on coding. Our primary outcome was receipt of genitourinary prosthetic device based on codes documented in claims from 2009 through 2015. Other factors of interest included patient age, comorbidity and geographic region. Results: We identified 23, 813 men who underwent radical prostatectomy in 2009 and 2010 (mean [SD] age 55.5 [9.1] years). Overall 731 men (3.07%) underwent genitourinary prosthetic surgery, including 243 (1.0%) for male slings, 111 (0.5%) for artificial urinary sphincter and 377 (1.6%) for penile prostheses. Median time to the first prosthetic surgery was 21.7 months (SD 12.9, range 1.2 to 54.5). Men undergoing prosthetic surgery for post-prostatectomy complications were older (57.1 vs 55.5 years, p=0.001) and more likely to be diabetic (31.9% vs 22.6%, p <0.001) than the remainder of the cohort. There was no significant difference in treatment with surgery based on overall comorbidity or geographic region (all p >0.05). Conclusions: Overall treatment with genitourinary prosthetic surgery for incontinence (1.5%) or erectile dysfunction (1.6%) was rare following radical prostatectomy. However, diabetic and older men demonstrated a greater likelihood of device placement.[LINE SEPARATOR]